2022
DOI: 10.3389/fpls.2021.781565
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Transformation of Recalcitrant Upland Switchgrass Using Morphogenic Genes

Abstract: Switchgrass (Panicum virgatum) is an excellent feedstock for biofuel production. While genetic transformation is routinely done in lowland switchgrass, upland cultivars remain recalcitrant to genetic transformation. Here we report the establishment of an efficient and reproducible transformation protocol for two upland cultivars, ‘Summer’ and ‘Blackwell’, by ectopic overexpression of morphogenic genes, Baby boom (Bbm) and Wuschel2 (Wus2). Two auxotrophic Agrobacterium strains, LBA4404Thy- and EHA105Thy-, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…The use of Wus2 and Bbm expanded the list of alternative explants for transformation, as demonstrated by the regeneration of fertile transgenic plants using mature embryo slices and leaf-base tissue segments in maize 10 . Using constructs developed by Lowe et al 10 , recent reports have shown leaf-base transformation in switchgrass 27 and successful gene mutagenesis in Eragrostis tef 28 . However, further improvements are needed to increase transformation frequency, to expand the method within the grass family and to eventually enable more complex genome editing applications.…”
Section: Identification Of Promoters That Stimulate Rapid Somatic Emb...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Wus2 and Bbm expanded the list of alternative explants for transformation, as demonstrated by the regeneration of fertile transgenic plants using mature embryo slices and leaf-base tissue segments in maize 10 . Using constructs developed by Lowe et al 10 , recent reports have shown leaf-base transformation in switchgrass 27 and successful gene mutagenesis in Eragrostis tef 28 . However, further improvements are needed to increase transformation frequency, to expand the method within the grass family and to eventually enable more complex genome editing applications.…”
Section: Identification Of Promoters That Stimulate Rapid Somatic Emb...mentioning
confidence: 99%
“…Lowe et al 10 have shown that the use of morphogenic genes Wus2 and Bbm facilitated direct Agrobacterium-mediated transformation of basal leaf tissue and the recovery of maize plants with random transgene integration. Recently, this method has been extended to random transformation in Panicum virgatum 27 and Cas9-mediated mutagenesis in Eragrostis tef 28 , demonstrating that Wus2/Bbm can facilitate direct leaf-base transformation in other grass species. However, to support the true potential of Cas9-mediated genome editing, substantially higher transformation rates are still required to produce the large numbers of plants necessary to recover complex genome modifications, such as targeted HDR-mediated gene insertion and large-scale chromosomal rearrangements 9 .…”
Section: Articlementioning
confidence: 99%
“…Genetic transformation is usually carried by Agrobacterium -mediated method, its transformation efficiency is often influenced by different factors, such as Agrobacterium strains, bacterial density, duration of infection, co-culture time, acetosyringone concentration, and the type of antibiotics [ 20 ], and so on. The gene was successfully transformed into Hevea brasiliensis using cotyledonary somatic embryos as explants [ 21 ], similarly, immature leaf segments of Switchgrass ( Panicum virgatum ) [ 22 ] and leaves of dandelion ( Taraxacum officinale ) were successfully transformed to obtain positive seedlings by optimizing various conditions [ 23 ]. Genetic transformation in sunflower is less reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, the genetic diversity and high self-incompatibility of switchgrass ecotypes have limited genetic studies and the development of mutant resources [ 6 , 7 ]. Transformation protocols and methods for CRISPR/Cas9- and RNAi-mediated gene editing in switchgrass have been reported [ 8 13 ]. For example, the pANIC vector collection has been successfully employed for the stable downregulation of lignin biosynthetic genes in transgenic embryogenic callus cultures [ 14 , 15 ] and have been used in transgenic RNAi studies to analyze and regulate cellulose and lignin biosynthesis in switchgrass [ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%